Influence of Radix Astragali on nitric oxide and endothelin-1 in pulmonary tissue in hypoxemic pulmonary hypertension in rats - Liu, Ji-Cheng (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2006)
OBJECTIVE: To study the influence of Radix Astragali (RA) on pulmonary tissue endothelin-1 (ET-1) and nitric oxide (NO) in hypoxic pulmonary hypertension rats